Attributions for Spousal Violence - Ratcliff, Linda L. (1997)
The literature on spousal violence suggests that abusive men, their female victims, and others in society often fail to blame abusers for their violent behavior. This failure perpetuates spousal violence because it allows abusers to continue being abusive without being held responsible for their actions. This study analyzed the attributions of male and female university students concerning written scenarios portraying moderate levels of spousal violence to determine whether observers tend to explain the violence using internal or external attributions. Male participants in the study reported a very low tendency, if any, to engage in spousal violence, while the female participants had very little, if any, experience as victims of abuse during the previous six months. Four theories were used to formulate the research questions concerning whether respondents would make internal or external attributions for spousal violence: Kelley's Covariation Theory, Jones and Nisbett's Actor-Observer Bias, Shaver's Defensive Attribution, and Backman's Self-Theory. The results indicated that the majority of male and female observers attributed the cause of violence to the abuser by making internal attributions for the abuse. These results offer an element of hope to the spousal violence literature. To the extent that members of society make internal attributions for spousal violence, abusers are held responsible for their behavior and ultimately may feel pressured to stop being abusive